Co-designing a landscape fire smoke health plan for at-risk populations in Australia - Sharon Campbell; Anna M Gjedrem; Bill Dodd; Fay H. Johnston (Environmental Research: Health, 2026)
Abstract Landscape fire smoke (LFS) has substantial health impacts for exposed and at-risk populations, with these events increasing in frequency and severity in a changing climate.While a variety of interventions are available for the management of health impacts during LFS events, effective utilisation of these options requires prior consideration and planning. This can be achieved through a customisable, individual planning tool, to be used by those most at risk of poor health outcomes during prolonged LFS events. As no such tool currently exists in Australia, we co-designed a resource with at-risk individuals, health professionals and content experts using a design-thinking framework. Consumer focus groups and in-depth interviews with general practitioners (GPs) were conducted, seeking their input on how LFS events were currently managed and what factors would be useful in a planning tool. We found the proposed tool to be valued by both consumers and GPs, and identified several possible avenues for improved communication of smoke events (e.g. early warning for at-risk populations). We describe the process and the output, with considerations towards future evaluation research. A LFS health plan is a valuable addition to available health management resources in a changing climate.